ANALISIS IMBAUAN PESAN EMOSIONAL TERHADAP RESPON SISWA STUNTING KELAS 1 SD DI KECAMATAN LEUWILIANG - Yusnita, Titien; Nurhalizah, Siti; Rohman, Ridho; Cahya, Robiatul; Melinda, Jenny (JURNAL KAJIAN ISLAM MODERN, 2024)
The study set out to evaluate the response of first-grade elementary school students who had experienced stunting to emotional message appeals delivered through games to enhance their comprehension. The research focused on first-grade students who had experienced stunting from ages 2 to 5 and had participated in a health consultation program with local midwives. Using a descriptive quantitative approach, the study analyzed the responses and attitudes of these students toward game materials accompanied by emotional messages. The findings conclusively demonstrated that emotional messages effectively boosted students' motivation to complete assigned tasks. However, it was also observed that emotional messages could elicit negative responses from students, thereby impacting their task completion.t, emotional messages are not always responded to positively by students but can also give rise to negative responses thereby affecting the speed of completing assignments given to students.